La Gloire de Don Ramire by Enrique Rodríguez Larreta - Gardie, Silvana (Universidad Nacional del Litoral, 2019)
Unlike many early 20th century Hispanic writers, Enrique Rodríguez Larreta achived - unintentionally, according to his words, his novel´s publicaction in the Mercure de France. This novel, La gloria de don Ramiro, was translated into French by the prestigious writer Remy de Gourmont in 1910. In Tiempos Iluminados, a kind of notes for Memorias, Larreta remembers a central episode in his literary life in Paris, linked precisely with that translation. In fact, his story is about a confession in which we can appreaciate the huge contrast between a dream come true because of that translation was made to the most prestigous literary language at that time, and an afront suffered from a review in a Parisian newspaper.